Impact resistance performance of green construction material using light weight oil palm shells reinforced bamboo concrete slab - Muda Z.C.; Usman F.; Beddu S.; Alam M.A.; Thiruchelvam S.; Sidek L.M.; Basri H.; Saadi S. (Institute of Physics Publishing, 2023)
This paper investigate the performance of lightweight oil palm shells (OPS) concrete with varied bamboo reinforcement content for the concrete slab of 300mm x 300mm size reinforced with different thickness subjected to low impact projectile test. A self-fabricated drop-weight impact test rig with a steel ball weight of 1.2 kg drop at 1 m height has been used in this research work. The main variables for the study is to find the relationship of the impact resistance against the amount of bamboo reinforcement and slab thickness. A linear relationship has been established between first and ultimate crack resistance against bamboo diameters and slab thickness by the experiment. The linear relationship has also been established between the service (first) crack and ultimate crack resistance against the bamboo reinforcement diameter for a constant spacing for various slab thickness using 0.45 OPS and 0.6 OPS bamboo reinforced concrete. The increment in bamboo diameter has more effect on the first crack resistance than the ultimate crack resistance. The linear relationship has also been established between the service (first) crack and ultimate crack resistance against the various slab thickness. Increment in slab thickness of the slab has more effect on the crack resistance as compare to the increment in the diameter of the bamboo reinforcement. Published under licence by IOP Publishing Ltd.